Dragonslayer : The Legend of Erich Ludendorff in the Weimar Republic and Third Reich - Lockenour, Jay, 1966- (Book collections on Project MUSE., 2021)
"This book demonstrates how Erich Ludendorff became the embodiment of Germans' fantasies of revenge for the defeat in World War I. Ludendorff's self-constructed legend and postwar activities provide new insights into the political cultures of the Weimar Republic and the Third Reich"--